Angka Lempeng Total Dan Cemaran Bakteri Pada Daging Domba di pasar Tradisional Kampung Lalang - Erika Triayu; Kurniawan Sinaga; Alfath Rusdhi (Journal of Pharmaceutical and Sciences, 2023)
Meat is an important food ingredient in meeting nutritional needs. The purpose of this study was to detect total plate count and bacterial contamination in lamb meat. The research method used in this research is descriptive method, because this research describes the characteristics of a population or a phenomenon that is the object of research that is experimental. Observational data were analyzed using a descriptive method of 6 samples of lamb meat obtained from the traditional market in Kampung Lalang and found Escherichia coli and Salmonella sp. The highest TPC analysis values ​​were found in traders 2 and 3 samples 2, namely 6.45x106 cfu/g and 7.05x106 cfu/g and the lowest amount of contamination was found in traders 1 sample 2, namely 4.5x105 cfu/g. In accordance with the limit for Escherichia coli 1x 101 colonies/gram and the limit for Salmonella sp negative/25 gram. The results showed that 95% of the lamb meat samples were contaminated with Escherichia coli and Salmonella sp. This shows that the lamb meat sold in Kampung Lalalang traditional markets does not meet the Indonesian National Standard (SNI) or is unfit for consumption.